2003
DOI: 10.1161/01.atv.0000075081.51227.86
|View full text |Cite|
|
Sign up to set email alerts
|

Genes, Environment, and Cardiovascular Disease

Abstract: Abstract-In this essay, we call to attention what every medical researcher knows about the etiology of cardiovascular disease but most deny, or choose to ignore, when designing, carrying out, and reporting genetic studies. Medical research is entering an era of synthesis that will take advantage of the successes of reductionism over the past decade in defining and describing human genome variations. Meaningful insights into the role of such variation requires a biological model of genome-phenotype relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
141
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(149 citation statements)
references
References 35 publications
5
141
0
3
Order By: Relevance
“…On the other hand, pairs of SNPs 1998-4951 and 3937-4951 may be measuring the same non-additive effects, because the r 2 value for the 1998-3937 pair is 0.704. Sing et al (1996Sing et al ( , 2003 and Wright et al (2003) have suggested that the genetic architecture of a complex trait consists of many genes with common alleles (relative allele frequencies greater than 0.01) that have a small effect on a particular phenotype, and a few genes with rare alleles that will have relatively larger effects. An alternative hypothesis assumes that genetic architecture of a complex trait is defined by a few genes with common alleles that have large phenotypic effects (Lander, 1996).…”
Section: Linkage Disequilibrium and Non-additivitymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, pairs of SNPs 1998-4951 and 3937-4951 may be measuring the same non-additive effects, because the r 2 value for the 1998-3937 pair is 0.704. Sing et al (1996Sing et al ( , 2003 and Wright et al (2003) have suggested that the genetic architecture of a complex trait consists of many genes with common alleles (relative allele frequencies greater than 0.01) that have a small effect on a particular phenotype, and a few genes with rare alleles that will have relatively larger effects. An alternative hypothesis assumes that genetic architecture of a complex trait is defined by a few genes with common alleles that have large phenotypic effects (Lander, 1996).…”
Section: Linkage Disequilibrium and Non-additivitymentioning
confidence: 99%
“…A major impediment in studying the contribution of genetic variation to interindividual variation in quantitative levels of apolipoproteins, and other risk factors for developing coronary heart disease, is that the available statistical models are not realistic representations of the biological complexity of genotype-phenotype relationships (Page et al 2003;Sing et al 2003). Phe-nomena such as allelic and genotypic heterogeneity, pleiotropy, gene by environment interaction and gene by gene interaction (epistasis) are realities that cannot easily be modelled, or estimated and tested, using population based samples of human data (Clark, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of cases, the disease is a result of the combined effect of multiple genetic and environmental factors, where each of the genetic factors makes a moderate contribution. [2][3][4][5] Recently, a large-scale, genome-wide association study of 65 671 gene-based single nucleotide polymorphisms in relation to myocardial infarction, a severe condition of CAD, was performed in a large group of Japanese cases (n ¼ 1133) and two control groups (n ¼ 1006 and 872, respectively). The study showed a strong association between susceptibility to myocardial infarction and polymorphisms in a 50 kb genomic region on chromosome 6p21 that contains the lymphotoxin-a (LTA) gene.…”
mentioning
confidence: 99%
“…143), in utero effects, diet-gene interactions, and the "environmental history"; that is, the life-long exposure to changing diets may alter expression of genetic information later in life (136). Maternal nutrition during pregnancy also has been linked to altered phenotypes in laboratory and farm animals (e.g., 27,30,69,164), and such epigenetic phenomena will likely affect gene-disease association studies.…”
Section: Invited Reviewmentioning
confidence: 99%
“…Maternal exposure to different nutrients and an organism's exposure during its lifetime to changing diets is likely to also produce different health outcomes because the exposure to food and xenobiotics may act upon the genome to alter gene expression. An excellent discussion of the complexity of genotype ϫ environmental history is presented by Sing and colleagues (136).…”
Section: Invited Reviewmentioning
confidence: 99%